Uniform Heating Model Analysis for the Formation Process of Aluminium Foam by Spot-Type Halogen Lamp - Nagahiro, R.; Nurrina, Rosli; Hangai, Y.; Yano, A.; Amagai, Kenji (Universiti Malaysia Pahang, 2019)
Heat treatment by heating furnace has limited the capability of heat treatment processes to control the desired heating volume and products’ sizes. This study introduced a heat treatment process using light heat sourced from a spot-type halogen lamp, with the aim of clarifying the thermal phenomenon of aluminium (Al) foam. Here, the temperature and deformation of Al foam were observed experimentally. In addition, thermal analysis was conducted numerically using a uniform heating model by neglecting the energy consumption of the blowing agent and deformation and thermal conductivity of Al. The experimental results revealed that the precursor initially formed at almost the same time as the phase change. The numerical results almost corresponded with the experimental results until the melting point of Al, after which a slight disagreement was observed. Moreover, the phase transformation appeared slightly earlier as a result of neglecting the deformation of Al foam and energy consumption of the blowing agent. Although the formation of Al foam cannot be expressed perfectly using the proposed uniform heating model, a qualitative phenomenon of such formation was successfully explained. In the future, the effects of deformation and energy consumption of the blowing agent and the thermal conductivity of Al can be considered in the proposed uniform heating model.